El origen de los mastines ibéricos. La trashumancia entre los pueblos prerromanos de la meseta - Cerdeño Serrano, María Luisa; Cordoba de Oya, Belén; Vega Toscano, Luis Gerardo (Complutum, 1998)
Sin resumen